Virtual Physics Laboratory Application Based on the Android Smartphone to Improve Learning Independence and Conceptual Understanding - Arista, Fitra Suci; Kuswanto, Heru (International Journal of Instruction, 2018)
The research study concerned here was to: (1) produce a virtual physics laboratory application to be called ViPhyLab by using the Android smartphone as basis; (2) determine the appropriateness and quality of the virtual physics laboratory application that had been developed; and (3) describe the improvement in learning independence and conceptual understanding of rotational dynamics after using the ViPhyLab application. The study was research and development (R&D) in design. The product was validated by a physics expert, an instructional media expert, peer reviewers, and physics teachers. The product underwent one-on-one testing, restricted testing, and field testing. The field testing used the one-group pre-test post-test design. The test subjects were forty students of Senior High School (Sekolah Menengah Atas, SMA, in Indonesia), Pekanbaru. The data collection was conducted by using a questionnaire, learning independence test, and conceptual understanding test. The appropriateness and quality of the application were analyzed descriptively. Improvement in learning independence and conceptual understanding was analyzed through paired t-test. Results of the study indicated: (1) ViPhyLab is an Android application that could be operated for learning both at and outside school; (2) the ViPhyLab application is quite viable as learning media and of very good quality.